Análise da comunidade de peixes e da teia trófica de um trecho do rio corrente - go - ALOÍSIO, Gustavo Ribeiro (2006)
In this work, fishes of Corrente river, affluent of Paranaíba River (Paraná basin, Brazil), were studied. Five surveys in the period of June of 2003 had been carried out until June of 2005. The sampling was executed in 8 points distributed in the stream, riverbed and lagoon. In each point had been used a set of gillnets with different mesh size (between 12 and 60mm opposite knots). The nets were inspected in the morning and the end of the day. The results had shown that 8 species were captured and the most abundant specie is Astyanax altiparanae; Shannon-Wienner index demonstrated diversity low; Morisita index indicated that there are high similarity between river, stream and lagoons; all species reproduce in the rainy season with exception of the Brycon nattereri; it is demonstrated the existence of piscivores species, herbivores, insectivores and detritus feeders.